2017
DOI: 10.4081/jphr.2017.995
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Unemployment and Well-Being after Job Loss during Economic Recession: Results of a Qualitative Study in East Central Sweden

Abstract: Introduction: Several studies have revealed an association between unemployment and ill health, and shown that unemployment can affect people differently. This study aimed to provide an understanding of the experiences of unemployment and perceptions of wellbeing among persons who involuntary lost their work during the recent economic recession in Gävle Municipality.Methods: Sixteen unemployed men and women aged 28-62 were interviewed face-to-face. A purposeful sampling strategy was used in order to suit the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
61
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 40 publications
6
61
0
1
Order By: Relevance
“…On the one hand, involuntary job loss during an economic recession may be less detrimental to health, because unemployment is less rare and the stigma of unemployment that could potentially harm (mental) health decreases [31]. On the other hand, the impact of unemployment on health may be increased during an economic recession as it may lead to increased insecurities about the chances for reemployment and therefore to increased psychological distress [32]. Previous studies have suggested that the post-2008 economic recession intensified the negative impact of unemployment on general and mental health [31, 33, 34] and that differences with respect to unhealthy behaviour, such as smoking and drinking, increased between the employed and unemployed [34].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, involuntary job loss during an economic recession may be less detrimental to health, because unemployment is less rare and the stigma of unemployment that could potentially harm (mental) health decreases [31]. On the other hand, the impact of unemployment on health may be increased during an economic recession as it may lead to increased insecurities about the chances for reemployment and therefore to increased psychological distress [32]. Previous studies have suggested that the post-2008 economic recession intensified the negative impact of unemployment on general and mental health [31, 33, 34] and that differences with respect to unhealthy behaviour, such as smoking and drinking, increased between the employed and unemployed [34].…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative study among participants over age 18 from the time of economic recession in Sweden illustrates the importance of gaining better understanding of the experiences of hardship and perceptions of health among those who lose their jobs [9]. Another qualitative study of unemployed persons, aged 18 and above with mental health problems, was performed in Germany [10].…”
Section: Introductionmentioning
confidence: 99%
“…It affects many millions of people around the world, threatens various states and ages, especially women and young people. The results of many studies presented so far have confirmed, among others the relationship between unemployment and poor health, especially mental health, as well as relationships with harmful health behaviors such as smoking and drinking problems (Nordenmark and Strandh, 1999;Winkelmann, 2009;Hammarström et al, 2011;Virtanen et al, 2013;Hiswåls et al, 2017;Dmytrów and Bieszk-Stolorz, 2019).…”
Section: Introductionmentioning
confidence: 64%